4(3x-2)=2(6x-6)

Simple and best practice solution for 4(3x-2)=2(6x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-2)=2(6x-6) equation:



4(3x-2)=2(6x-6)
We move all terms to the left:
4(3x-2)-(2(6x-6))=0
We multiply parentheses
12x-(2(6x-6))-8=0
We calculate terms in parentheses: -(2(6x-6)), so:
2(6x-6)
We multiply parentheses
12x-12
Back to the equation:
-(12x-12)
We get rid of parentheses
12x-12x+12-8=0
We add all the numbers together, and all the variables
4!=0
There is no solution for this equation

See similar equations:

| 0f-5=-1+2f | | -4(3x-1)=-103 | | (n-4)=2 | | -2z-9=-5z+9 | | x+7+3x-15=360 | | 6(6x-8)=-48 | | y-3=10(-2) | | 2a-2=7+2a | | (4x+5)+1=18 | | -8w=10-9w | | 726=1/3(x+1632) | | 4(3x-2)=2(6x-5) | | 5+7x-5xx=5 | | 4(x3)=44 | | 94+20+x=180 | | -y-3=9+2y | | 6(2x-3)=-18 | | X+(5x+5)x=4 | | 4(3x-2)=2(6x-3) | | 140=70+x | | 4(3x-2)=2(6x-2) | | x=80+25 | | 8-4w=-5w | | 4(1+4p)-4=48 | | (5x-2x)(x)x=3 | | 2(20x+30=420 | | -(x+4=1 | | 4h+10=-h | | 2x+12=7x-3=180 | | 4h-10=-h | | 5w+3=-18 | | -5h+7=-3(h-1) |

Equations solver categories